Comparative Proteomic Analysis of Grapevine Rootstock in Response to Waterlogging Stress - Wang, Xicheng; Yan, Lichun; Wang, Bo; Qian, Yaming; Wang, Zhuangwei; Wu, Weimin (Frontiers in Plant Science, 2021)
Waterlogging severely affects global agricultural production. Clarifying the regulatory mechanism of grape in response to waterlogging stress will help to improve the waterlogging tolerance of grape. In the present study, the physiological and proteomic responses of SO4 grape rootstock to different waterlogging tolerances were comparatively assayed. The results showed that the activities of SOD and POD first increased and then decreased, while the change trend of CAT and APX activities was the opposite. In addition, the MDA and H2O2 contents increased after waterlogging treatment, but the chlorophyll a and chlorophyll b contents decreased. A total of 5,578 grape proteins were identified by the use of the tandem mass tag (TMT) labeling technique. Among them, 214 (103 and 111 whose expression was upregulated and downregulated, respectively), 314 (129 and 185 whose expression was upregulated and downregulated, respectively) and 529 (248 and 281 whose expression was upregulated and downregulated, respectively) differentially expressed proteins (DEPs) were identified in T0d vs. T10d, T10d vs. T20d and T0d vs. T20d comparison groups, respectively. Enrichment analysis showed that these DEPs were mainly involved in glutathione metabolism, carbon fixation, amino sugar and nucleotide sugar metabolism, biosynthesis of amino acids, photosynthesis, carbon metabolism, starch and sucrose metabolism, galactose metabolism, protein processing and ribosomes. To further verify the proteomic data, the expression of corresponding genes that encode eight DEPs was confirmed by quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR). The results of this study presented an important step toward understanding the resistance mechanisms of grape in response to waterlogging stress at the proteome level.